Biodiversity and ITS-RFLP characterisation of Aspergillus section Nigri isolates in grapes from four traditional grape-producing areas in Greece. - Dimosthenis Kizis; Pantelis Natskoulis; George-John E Nychas; Efstathios Z Panagou (PLoS ONE)
A study on the occurrence of Aspergillus section Nigri species on grapes from four traditional grape-producing areas in Greece during the 2011/2012 vintage, and their capability to produce OTA was conducted. One hundred and twenty-eight black aspergilli isolates were characterised at the species level initially by the use of morphological criteria in accordance with appropriate keys, followed by molecular characterisation performed with Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) of the 5.8 ribosomal RNA gene Internal Transcribed Spacer region (5.8 rRNA ITS). Restriction enzyme digestion of the ITS amplicons using the HhaI, HinfI and RsaI, endonucleases distinguished eleven different patterns of restriction fragment length polymorphism (RFLP), four for each of the HhaI and RsaI digests and three for HinfI. From a total number of 128 individual isolates, 124 were classified into four Aspergillus species corresponding to A. carbonarius, A. tubingensis, A. japonicus and A. ibericus, and the remaining 4 were classified as members of the A. niger aggregate. A. carbonarius and A. tubingensis being the main representative species were equally counted, with higher geographical representation of the former in southern and the latter in northern regions, respectively. All isolates were tested for their ochratoxigenic potential by use of High Performance Liquid Chromatography (HPLC) and Enzyme Linked Immuno Sorbent Assay (ELISA), resulting in significant interspecies differences in OTA production.